Seaweed Selection to Supply Superior Seeds for Cultivation - Nelly Hidayanti Sarira; Petrus Rani Pong-Masak (Jurnal Perikanan Universitas Gadjah Mada, 2018)
Seaweed Kappaphycus alvarezii is a pre-eminent commodity in the field of marine and fisheries Indonesia which has been widely cultivated in coastal waters. Currently, the main problem faced by the cultivators is the limited stock of seeds, both in terms of quality and quantity. Selection is one method that is expected to increase the rate of seaweed growth quickly, cheap, easy, bulk, and sustainable.This study aims to determine the effect of selection on the growth of seaweed so that it can be done superior seed production for cultivation purposes. Seaweed cultivation was done in Kulu Village, Wori District, North Minahasa Regency, North Sulawesi by using long line method in April-June 2015. Selection is based on the daily growth rate parameter (DGR) and the selection method refers to the selection protocol that has been developed on K. alvarezii seaweed. Results showed that DGR of selection seedlings were higher (P <0.05) compared to controls, in which DGR of selection reached 5.87%/day, while DGR of control was 1.89%/day. From three seed production cycles (G-1 - G-3), the average DGR resulted from the selection was 5.53%/day and control 2.19%/day. Carrageenan content of selection result is relatively higher (47.66%) than control (31.28%) with mean for three cycle (G-1 - G-3) that is 43.55% for selection and 33.20% for control. Water quality (temperature, salinity, nitrate, phosphate) during the study is still within the appropriate range for seaweed growth. Therefore it is concluded that with the application of the method of seaweed selection can increase the daily growth rate and carrageenan content of seaweed K. alvarezii which directly affects the increase of production both in quantity and quality.